The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fonc.2022.935373
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Treatment Outcomes of Myeloid Sarcoma in Children: The Experience of the Polish Pediatric Leukemia and Lymphoma Study Group

Abstract: IntroductionMyeloid sarcoma (MS) is an extramedullary malignant tumor composed of immature myeloid cells. It occurs in patients with acute myeloid leukemia (AML), myelodysplastic syndrome (MDS), or chronic myeloid leukemia (CML). MS may coincide with disease diagnosis or precede bone marrow involvement by months or even years; it can also represent the extramedullary manifestation of a relapse (1, 2).AimThe aim of this study is to describe clinical characteristics of children diagnosed with MS in Poland as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Patients with orbital MS mostly presented with AML M2 and M5 subtypes, and AML M5 subtype have a higher initial white blood cell count. These are consistent with previous reports ( 3 , 5 , 9 , 11 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Patients with orbital MS mostly presented with AML M2 and M5 subtypes, and AML M5 subtype have a higher initial white blood cell count. These are consistent with previous reports ( 3 , 5 , 9 , 11 ).…”
Section: Discussionsupporting
confidence: 94%
“…According to the single-center data of 11 children diagnosed with MS, the most common subtype was MS accompanied by AML, which supported the previous literature ( 9 11 ). Approximately 6.7%–12% of childhood AML patients had MS at diagnosis ( 12 15 ).…”
Section: Discussionsupporting
confidence: 88%
“…The most common mutation and translocation described in MS are mutated NPM1 and t(8:21), respectively [ 22 , 23 ]. There is uncertainty regarding the value of t(8;21) in MS, even though it has a favorable prognostic significance for AML [ 24 ]. Inversion-16 translocation is associated with MS, particularly in abdominal sites [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of 345 patients with isolated MS in the SEER database showed that patients with MS had a better survival rate than those without MS [ 31 ]. Sambroska et al reported worse outcome in patients with isolated MS compared to patients with MS with AML (56% and 84%, respectively) [ 24 ]. Other studies considered MS a poor prognostic factor with lower EFS and OS [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…One review of all pediatric myeloid sarcomas in Poland demonstrated an additional 12 pediatric isolated MS cases. 16 Our patient relapsed at the end of therapy, presenting us with a treatment dilemma as no therapeutic guidelines for relapsed MS exist.…”
mentioning
confidence: 92%